PEMANFAATAN MEDIA PRESENTASI INTERAKTIF (MPI) AUDIO VISUAL POWER POINT MENINGKATKAN PRESTASI BELAJAR PAI SISWA KELAS VA SD N LEMPUYANGWANGI SEMESTER I TAHUN PELAJARAN 2021/2022 - Budiningsih, Dwi (Program Studi Akuntansi IKOPIN, 2021)
The purpose of this paper is to use Audio Visual Power Point Interactive Presentation Media(MPI) to improve the learning achievement of fifth grade students at SD N LempuyangwangiSemester I for the 2021/2022 academic year. At SD N Lempuyangwangi Class VA, by usingthe Audio Visual Power Point Interactive Presentation Media (MPI) it is clear that thechildren's enthusiasm for learning increases, children can focus more on teaching materialsso that activeness and learning outcomes increase, this can be seen from the value of studentachievement when doing the final evaluation of the learning turned out to be above theaverage Minimum Completeness Criteria (KKM) that had been applied previously. Theconclusions from the explanation that the author has poured on the previous page are asfollows: By utilizing Power Point students become active, creative and learning becomes fun,Skills in using computers and information technology are a necessity in developing teachersand their learning, Utilizing Power Point increases children's learning motivation andarouse curiosity about many things, Provide appreciation and inspiration to be able to createtheir own for teachers and students